Strong transfer channels in the $^{6,7}$Li+$^{28}$Si system at near-barrier energies - A. Pakou; K. Rusek; N. Alamanos; Aslanoglou, X.; S. Harissopulos; Kokkoris, M.; A. Lagoyannis; Mertzimekis, T. J.; Musumarra, A.; Nicolis, N.G.; Papachristodoulou, C.; Pierroutsakou, D.; et al. (Phys. Rev. C, 2007)
Exclusive ?-particle and proton production measurements of the system Li6+Si28 are performed at near-barrier energies. Each reaction channel is tagged via a particle-? coincidence requirement. Ratios of direct to compound contributions are estimated via particle angular distribution measurements. Strong reaction channels for n and p transfer are identified and quantified and found to be described well on a qualitative basis with distorted-wave Born approximation calculations. © 2007 The American Physical Society.